Monetary policy surprises, central bank information shocks, and economic activity in a small open economy - Stefan Laséen (Sveriges Riksbank, 2020)
In this paper I study the effects of monetary policy on economic activity and asset prices in Sweden, separately identifying the effects of a conventional policy change from effects of new information about economic fundamentals. Recent research has shown that high-frequency changes in policy interest rate futures prices around central bank policy announcements might not only contain monetary policy shocks but also central bank information shocks. I add to this line of research by studying a case where the central bank, in contrast to many other central banks studied in this literature, is very open and transparent about the monetary policy decision and publishes a full set of forecasts including the interest rate at the same moment as the decision is revealed. I use this information to construct an informationally-robust instrument for monetary policy shocks as the component of high-frequency market surprises triggered by policy announcements that is orthogonal to both central bank's economic projections, including policy rate projections, and to past market surprises. I also add sign restrictions on stock market changes around the announcement to separate structural monetary policy shock from central bank information shocks. In contrast to recent work for other countries, I do not find that separating monetary policy shocks from central bank information shocks is important to measure the effects of monetary policy in Sweden.
Keywords: C32; C36; D83; E31; E43; E44; E52; E58; G14; 330; Monetary Policy; External Instruments; Monetary Policy Surprises; Information Effect; Small Open Economy; Exchange Rate; Stock Prices; House Prices